The Generational Narrative in Criticism of New Realism - Kalafatics, Zsuzsanna (Slavica, 2021)
At the end of the 20th century, New Realism emerged in contrast to postmodern literature. The representatives of this school defined themselves in their manifestoes and critical writings as a generation with the same aesthetic and ideological principles. The anthology of New Russian Criticism, edited by Roman Senchin, is a demonstration of this common action. The present study aims to present how and what elements of this generational consciousness and cultural identity are created, i.e. how thinking about literature has changed.